THE IMPLEMENTATION OF CHARACTER VALUES IN ENGLISH LANGUAGE INSTRUCTION TO THE SEVENT GRADE STUDENTS AT STATE HIGH 6 OF PALEMBANG - Nur Azizah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
This qualitative research was conducted in order to evaluate the implementation of character values in the English language instructional activities at SMP Negeri 6 Palembang.The subjects of the research were the seventh grade students and the English teacher. The researcher analyzed the lesson plans and the implementation to investigate how character values were inserted in teaching of the four basic skills in English. The character values included to be observed in this study were about religous behaviour, honesty, tolerance, discipline, hard working, creativity, independence, democracy, curiousity, patriotism, appreciation towards achievement, courteous/communicative ability, love peace, love reading, conservation, social care, logical thinking,and responsibility. The instrument of the study consisted of field notes, and interview guide. The analysis indicated that the teacher did not explicitly insert the character values into theindicators and assessment instrument. However, some values were reflected in the teaching and learning activities, and in the implementationof teaching the four skills in the classroom. Character values in learning only becomes a mere discourse will not work because there no continuity and harmoniation betwee students, teachers, schools and students’ parent.